PHISHING BEHAVIOR ON SOCIAL MEDIA: CASE STUDY ON MSME PRODUCTS IN INDONESIA THROUGH TIKTOK SHOP - Fina Fayza Amalia; I Wayan Sukadana (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The aim of this research is to find out the reasons for the rejection of the closure of the TikTok Shop on October 4 2023 by MSME players in Indonesia purely because of rational business or irrational business problems (behavior economics). This research uses a case study approach using snowball sampling techniques, data triagulation, and descriptive statistical analysis of two-average difference tests on MSME products in Indonesia through the TikTok Shop. The research results show that the rejection of the TikTok Shop on October 4 2023 was caused purely by rational business reasons related to income, but on the other hand, of course there are irrational business problems from phishing behavior motives. This motif is designed through the TikTok Shop algorithm which can have a positive impact and can indirectly harm users. It is true that the TikTok Shop algorithm has a positive influence on digital marketing communications in Indonesia, such as the recommendation algorithm. The TikTok algorithm has great potential to help marketers achieve marketing goals more effectively with creative, interactive and audience-relevant marketing communications being the key to success in achieving marketing goals on TikTok. TikTok's success in capturing users' attention is not only based on its unique short video concept, but also on the power of its sophisticated algorithm. This sophistication could certainly be a boomerang for MSMEs without them realizing it. The case of closing the TikTok Shop resulted in a correlation relationship (only matching) at certain times between the number of TikTok Shop users and the number of Shopee users.